Hubungan Antara Motivasi, Dukungan Keluarga Dan Kecemasan Mahasiswa Dalam Menghadapi Ujian Proposal Di Prodi Keperawatan Waingapu - Yosephina Elizabeth Sumartini Gunawan; Melkisedek Landi; Diane Anthasari (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2018)
Introduction: students are vulnerable to anxiety due to various demands, especially in facing the exam of a proposal or a final assignment at a college. The motivation and family support are the factors that affect students' anxiety in facing the exam proposal or final project. The purpose of this study is to know the relationship between motivation and family support with the anxiety of third-grade students in facing the exam proposal in Nursing Program Study of Waingapu. Methods: This study was a pre-experimental study with the cross-sectional design. The sample was 44 respondents with a sampling technique using consecutive sampling method. Instruments used in the form of questionnaires and research variables consisted of motivation, family support and anxiety using Spearman's rho analysis technique. Result: the research conducted on 44 respondents shows that there is no correlation between motivation (P= 0,254) and family support (P= 0,674) with student level anxiety in facing exams of the proposal of Nursing Program Study of Waingapu. Conclusion: The researcher concludes that there is no correlation between motivation and family support with students' anxiety level III in facing the exam proposal in Nursing Program Study of Waingapu.